Synthesis, Characterization and Antimicrobial Analysis of 1-(1-Phenylazo)-2-Naphthol - I. C, Onunkwo; C. M, Ejikeme (International Journal of Chemistry and Materials Research, 2020)
Pathogenic microorganisms are capable of causing various illnesses and diseases to its hosts (humans, animals and plants) and has prompted researchers in search of antibiotics to be used in treatment of such ill-health conditions. Azo dyes possess some interesting colours and usages in many industries. In the present study, 1-(1-Phenylazo)-2-naphthol azo dye was synthesized by diazotization of aniline and coupling reaction with 2-naphthol. The results obtained from the UV-vis, IR and NMR spectra were able to elucidate the important peaks in the compound. The concentrations of 200 μg/mL, 30 μg/mL control drugs [Augmentin (Au) and Oflocitoxin (OFX)] and raw sample of the compound were able to inhibit Staphylococcus aureus at 0.1 mm, 15 mm, 13 mm and 0.4 mm marks respectively while the concentrations of 200 μg/mL, 30 μg/mL Augmentin (Au, control drug), 30 μg/mL Oflocitoxin (OFX, control drug) and raw sample of the compound had inhibitions of 0.2 mm, 21 mm, 19 mm and 0.4 mm marks respectively against Escherichia coli; Aspergillus fumigatus was resistant across all prepared concentrations and raw sample of the compounds, including the 30 μg/mL control drugs [Augmentin (Au) and Oflocitoxin (OFX)] from the antimicrobial analysis carried out. The minimum inhibitory concentrations of the compound was estimated at 200 μg/mL concentration.